Effects of Pulsatile Bioreactor Culture on Vascular Smooth Muscle Cells Seeded on Electrospun Poly(lactide-co-epsilon-caprolactone) Scaffold - Mun, Cho Hay; Jung, Youngmee; Kim, Sang-Heon; Kim, Hee Chan; Kim, Soo Hyun (WILEY, 2013)
Electrospun nanofibrous scaffolds have several advantages, such as an extremely high surface-to-volume ratio, tunable porosity, and malleability to conform over a wide variety of sizes and shapes. However, there are limitations to culturing the cells on the scaffold, including the inability of the cells to infiltrate because of the scaffold's nano-sized pores. To overcome the limitations, we developed a controlled pulsatile bioreactor that produces static and dynamic flow, which improves transfer of such nutrients and oxygen, and a tubular-shaped vascular graft using cell matrix engineering. Electrospun scaffolds were seeded with smooth muscle cells (SMCs), cultured under dynamic or static conditions for 14 days, and analyzed. Mechanical examination revealed higher burst strength in the vascular grafts cultured under dynamic conditions than under static conditions. Also, immunohistology stain for alpa smooth muscle actin showed the difference of SMC distribution and existence on the scaffold between the static and dynamic culture conditions. The higher proliferation rate of SMCs in dynamic culture rather than static culture could be explained by the design of the bioreactor which mimics the physical environment such as media flow and pressure through the lumen of the construct. This supports regulation of collagen and leads to a significant increase in tensile strength of the engineered tissues. These results showed that the SMCs/electrospinning poly (lactide-co-epsilon-caprolactone) scaffold constructs formed tubular-shaped vascular grafts and could be useful in vascular tissue engineering.
Keywords: PERFUSION BIOREACTOR; EPSILON-CAPROLACTONE; BLOOD-VESSEL; STEM-CELLS; GRAFTS; SYSTEM; PRESSURE; COLLAGEN; WALL